UJI EFEKTIVITAS SEDIAAN GEL MINYAK ATSIRI KULIT BUAH JERUK PONTIANAK (Citrus nobilis Lour. Var. microcarpa) TERHADAP Escherichia coli DAN Staphylococcus aureus - Wintari Taurina; Rafikasari Rafikasari (Majalah Obat Tradisional, 2014)
Essential oil is a natural substance that has been known as antibacterial. This research aimed to examine the effectiveness of antiseptic gel from essential oil which taken from rind Pontianak orange. Essential oil from rind Pontianak orange are formulated into a gel and it tested its effectiveness as an antibacterial to Escherichia coli and Staphylococcus aureus. Based on the result of the study, the effective concentration of essential oil to inhibit Escherichia coli is 0,5%, while Staphylococcus aureus is inhibited at concentration 0,1%, 0,3% and 0,5%. The results of the gel test stabilization showed that the homogenity of gel, pH value and stable adhesion are good. Coverage gel increased during 30 days of storage. One Way Anova test analysis showed that the dispersive power of each gel formula does not differ significantly.